The Effect of Work-Life Balance and Work Environment on Employee Job Satisfaction at PT Honda Sanggar Laut Palopo - Nurmala; Muhammad Kasran; Adil Basir (LP2M IAIN Palopo, 2025)
An imbalance in work-life balance can lead to decreased health and quality of work. A healthy work environment also plays an important role in increasing productivity and job satisfaction. This study aims to test the influence of work-life balance and work environment on employee job satisfaction at PT Honda Sanggar Laut Palopo. In this study,This study uses a quantitative method that focuses on data collection and statistical analysis that aims to answer the researcher's questions and test the hypothesis. The population in this study was 60 employees of PT. Honda Sanggar Laut Palopo. The sample in this study was 50 employees of PT. Honda Sanggar Laut Palopo. Data collection was carried out using a google form through the distribution of questionnaires to respondents who were measured, each item was scored on a Likert scale where each question was scored from (1) to (5). The technical analysis of this research data was tested using Smartpls4.The results of this study indicate that work-life balance has a positive and significant influence on the job satisfaction of employees of PT Honda Sanggar Laut Palopo and the work environment has a positive and significant influence on the job satisfaction of employees of PT Honda Sanggar Laut Palopo.